Addition of vitamin B12 to exercise training improves cycle ergometer endurance in advanced COPD patients: A randomized and controlled study. (January 2017) - Paulin, Fernanda Viana; Zagatto, Alessandro Moura; Chiappa, Gaspar R.; Müller, Paulo de Tarso
Abstract: Vitamin B12 is essential in the homocysteine, mitochondrial, muscle and hematopoietic metabolisms, and its effects on exercise tolerance and kinetics adjustments of oxygen consumption ( V 'O2p ) in rest-to-exercise transition in COPD patients are unknown. This randomized, double-blind, controlled study aimed to verify a possible interaction between vitamin B12 supplementation and these outcomes. After recruiting 69 patients, 35 subjects with moderate-to-severe COPD were eligible and 32 patients concluded the study, divided into four groups (n = 8 for each group): 1. rehabilitation group; 2. rehabilitation plus B12 group; 3. B12 group; and 4. placebo group. The primary endpoint was cycle ergometry endurance before and after 8 weeks and the secondary endpoints were oxygen uptake kinetics parameters (time constant). The prevalence of vitamin B12 deficiency was high (34.4%) and there was a statistically significant interaction ( p  < 0.05), favoring a global effect of supplementation on exercise tolerance in the supplemented groups compared to the non-supplemented groups, even after adjusting for confounding variables ( p  < 0.05). The same was not found for the kinetics adjustment variables (τ V 'O2p andMRT V 'O2p, p  > 0.05 for both). Supplementation with vitamin B12 appears to lead to discrete positive effects on exercise tolerance in groups of subjects with more advanced COPD and further studies are needed to establish indications for long-term supplementation. Highlights: This study confirms the effects of Pulmonary Rehabilitation on acceleration of V ´O2 kinetics. Vitamin B12 deficiency is a real problem in COPD populations. Vitamin B12 supplementation can improve the effects of training, but new studies with large number of subjects are necessary. Adjustments on V ´O2 kinetics are non-affected by combined supplementation of vitamin B12 and training.